Classificação da variabilidade da frequência cardíaca em praticantes de natação - Scorcine, Claudio Ramos Oliveira [UNIFESP] (2016)
The cardiovascular system is controlled in part by the autonomic nervous system, through the sympathetic and parasympathetic pathways. These controllers are closely associated with the behavior of heart rate. One way to gauge the performance of most of the routes is through the heart rate variability (HRV) and many studies have shown a relationship between increased activation of the sympathetic system with decreased HRV. This decrease is directly linked to various diseases such as diabetes, hypertension, chronic obstructive pulmonary disease, obesity and others. Another research line deals with the influence of physical activity on the HRV parameters, and has been observed that physical exercise can be positive for the increased rates of HRV. However, in the literature can?t yet predict what the HRV levels that trained individuals must present nor the HRV levels that can be related to any pathology. The objective of this work was to develop a rating scale of HRV indexes in swimming practitioners of both genders. After approval of the Ethics Committee of UNIFESP and signing the Consent and Informed by volunteers, 100 subjects were selected, 70 male and 30 female, separated into three distinct levels of experience (beginner, intermediate and advanced). Statistical analysis was performed using Mann Whitney U test, it was not possible shown significant differences in the rates of HRV between males and females. The data were analyzed in Kubios 2.0 program. After no confirmation of the normality of the data by the Kolmogorov-Smirnov test it was decided to use the Mann-Whitney U test for comparison of HRV index for the gender studied and intensity of training. For to compare the time of practice was used ANOVA with post hoc Bonferroni. Results: There no were observed significant differences in HRV index between male and female, training intensity and time of practice. For the classification table of HRV indexes was used to cluster statistic considering five levels of classification, as follows: Far below the median; below the median; median; above the median and very above the median.